Pengaruh Pajak, Ukuran Perusahaan, dan Dewan Komisaris Independen terhadap Transfer Pricing - Mochamad Febrianto; Lioni Indrayani (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of Tax, Firm Size, and Independent Board of Commissioners on Transfer Pricing in energy sector companies listed on the Indonesia Stock Exchange during the period 2019–2023. The research employs a quantitative method with a panel data regression approach to examine the relationship between these variables and their effect on transfer pricing decisions. A purposive sampling technique was used to select a sample of 14 companies, resulting in a total of 70 observations. The data were sourced from the companies' financial statements and annual reports, and analyzed using E-Views 12 software. The findings of this study show that tax, firm size, and the independent board of commissioners have a simultaneous effect on transfer pricing, indicating that these factors collectively influence how energy sector companies manage their pricing strategies for intercompany transactions. When considered individually, tax and firm size were found to significantly affect transfer pricing, suggesting that companies with higher tax burdens and larger sizes tend to engage in transfer pricing practices. However, the study found that the independent board of commissioners had no significant effect on transfer pricing. These results offer insights for policymakers and investors to better understand the dynamics of transfer pricing within the energy sector.